Zinc-Induced Histopathological and Enzymatic Alterations in Kidney and Liver of Common Carp Cyprinus carpio var. Communis: A Comprehensive Analysis - Khurshid, Ibraq; Noorani, Irfan Ahmed (Asian Journal of Biological and Life Sciences, 2025)
Aim: Investigate effects of sublethal ZnSO4 exposure on serum enzymes (ALP, AST, ALT) and histopathology of liver and kidney in Cyprinus carpio. Materials and Methods: Fish exposed to ZnSO4 for 21 days; enzyme assays and histological analyses performed. Results: Elevated serum enzymes and histopathological lesions (hepatocyte degeneration, glomerular lesions) observed indicating tissue damage. Conclusion: Zn exposure causes oxidative stress and organ damage in common carp.
Keywords: Cyprinus carpio; Zinc; Histopathology